2019
DOI: 10.1111/febs.14825
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA ES1 controls the proliferation of breast cancer cells by regulating the Oct4/Sox2/miR‐302 axis

Abstract: ES1 is a long non‐coding RNA (lncRNA) that regulates pluripotency of human embryonic stem cells, which is known to be a downstream target of stemness factors Oct4 and Nanog, and serves as a modular scaffold for Sox2. However, the role of ES1 in cancer biology is not fully characterized. The results of our study show that ES1 transcript is upregulated in both high‐grade and P53‐mutated breast tumor tissues. Knockdown experiments show that ES1 suppression in breast cancer cells restricts cancer cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…[82] -C01108) miR-200; Regulates stemness factors SOX2 and OCT4 and their downstream targets, miR-306, miR-106b [81].…”
Section: Linc00511mentioning
confidence: 99%
See 1 more Smart Citation
“…[82] -C01108) miR-200; Regulates stemness factors SOX2 and OCT4 and their downstream targets, miR-306, miR-106b [81].…”
Section: Linc00511mentioning
confidence: 99%
“…The role of lncRNA ES1 (also called LINC01108 or ENST01108) has been studied in human embryonic stem cells [104]. Knockdown of the lncRNA in TNBC MDA-MD-231 and HER2+ SKBR3 cell lines reduced stemness factors SOX2 and OCT4 and their targets, miR-302 and miR-106b, were downregulated [81]. Further, the upregulation of lncRNA ES1 increased expression of Snail/Zeb1 and miR-106b and suppressed the expression of E-cadherin and miR-200, thereby implicating ES1 as a driver of EMT.…”
Section: Lncrna Es1/linc01108mentioning
confidence: 99%
“…The downregulation of miR‐302b by its upstream regulator, MIAT, can also promote BC cell migration . High lncRNA ES1 transcript levels in high‐grade and P53‐mutated BC tissues can lead to miR‐302 upregulation and promote cell proliferation and migration . In specific BC cell lines, some scholars have found that vitamin C can reduce the reprogramming efficiency of the miR‐302/367 cluster by downregulating TET1 gene expression, which reverses the inhibition of cell invasion and proliferation by this cluster .…”
Section: Functions and Mechanisms Of Mir‐302 Cluster In Tumor Developmentioning
confidence: 99%
“…Similarly, the EC‐specific miR‐302c inhibits HCC growth and angiogenesis by regulating EndMT through MTDH . The upregulation of miR‐302 by lncRNA ES1 promotes EMT in BC cells . Jhdm1a/1b, a vitamin C‐dependent H3K36 demethylase, can cooperate with Oct4 to activate the miR‐302/367 cluster, leading to cell reprogramming .…”
Section: Functions and Mechanisms Of Mir‐302 Cluster In Tumor Developmentioning
confidence: 99%
“…In addition to these, various lncRNAs such as LUCAT1, lncRNA-Hh, FGF13-AS1, lncRNA ES1 NEAT1 have been reported to be commonly involved in up-regulation of signaling pathways and modulation of stem cell factors (Wnt/β-catenin, Hedgehog, myc, SOX2, OCT4, KLF4, and NANOG). Their role in the promotion of stemness in BC cells and subsequent tumor progression, invasion and metastasis is critical for tumor maintenance and therapeutics [223][224][225][226][227].…”
Section: Role Of Micrornas and Lncrna In Bcscsmentioning
confidence: 99%